xIndices: Version 1.2.1 - Dixit, Jivesh (Zenodo, 2024)
xIndices is a xarray based Python library for calculating climate variability indices and patterns. For now, from preprocessing the data to final calculation of indices and patterns, it allows user to directly calculate without diving into the steps for calculations. Installation: conda create -n x_indices python=3.11 ###(OPTIONAL) conda activate x_indices ###(If creating the x_indices environment) conda install -c jiveshdixit -c conda-forge xindices